2022
DOI: 10.3390/ijerph19138146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residential Environmental Screening and Perception Surveys on Superfund Environmental Health Risk Perceptions

Abstract: Residents at one of the nation’s largest and longest-operating Superfund sites (Butte, Montana) have expressed environmental health risk perceptions that often diverge from those of EPA and other official stakeholders responsible for the investigation and remediation of site contamination aimed at protecting human health and the environment. A random sample of Butte residents participated in a study of how home-based environmental screening influences environmental health perceptions. Participants completed su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The environmental advantages of these activities were brought to light by this campaign [57]. Residents' opinions of environmental health have also improved as a result of education regarding the precise kinds and concentrations of pollution in their homes [58]. By informing the public about the threat of air pollution and increasing stakeholder engagement, governments can more effectively utilize financial resources and implement more sustainable solutions [59].…”
Section: Discussionmentioning
confidence: 99%
“…The environmental advantages of these activities were brought to light by this campaign [57]. Residents' opinions of environmental health have also improved as a result of education regarding the precise kinds and concentrations of pollution in their homes [58]. By informing the public about the threat of air pollution and increasing stakeholder engagement, governments can more effectively utilize financial resources and implement more sustainable solutions [59].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study [53], it was revealed that "community acceptance," which requires the agency to ensure that the "affected community" has been involved in the process from the beginning, understands the process reasonably, and has the opportunity to contribute meaningfully to agency decision-making. When referencing this study, it is possible to consider the mediating role of community acceptance between transparency and the intention to participate in policy-making.…”
Section: Limitationsmentioning
confidence: 99%
“…This view is simply summarized as the “compliance cost argument”. Chintrakam and Weber [ 19 ] found by investigating the manufacturing statistics of 48 states in the United States that the strengthening of environmental regulation will make the manufacturing industry inefficient, which may be due to a lack of sufficient funds for the development of environmental protection patents due to environmental regulation [ 20 ]. Kneller and Manderson [ 6 ] examine environmental regulation and creative activities in the UK manufacturing sector from 2000 to 2006 and show that ER can crowd out firms’ investment in innovation, particularly in industries with high environmental costs.…”
Section: Introductionmentioning
confidence: 99%